Stable isotope compositions of dominant zooplankton species in relation to environmental factors in the Dardanelles - Uzundumlu, Sinan; Büyükateş, Yeşim (Archives of Biological Sciences, 2019)
Paper description: Stable isotopes in marine ecosystem are used to determine the food web and trophic interactions among marine species. Stable isotope studies on marine ecosystem are conducted on size-based groups of species. The present study was conducted on species abundant in the study area in the Dardanelles Strait. Although the stations were close to each other, the δ13C and δ15N signatures of the primary consumers varied. As this study was conducted at the species level, it differs from previous studies in the Mediterranean and the Aegean Sea. The results can provide an important reference for future work in the region. Abstract: Samples were collected seasonally from three stations in the Dardanelles between April 2016 and October 2017 to determine the effects of biological and physicochemical properties of the coastal system on the isotopic compositions of the most abundant copepod species, Acartia clausi and Calanus helgolandicus, and a cladoceran, Penilia avirostris. Plankton samples were collected horizontally with a 200-µm-mesh plankton net and isotopic analyses were performed by mass spectrometry after identification to species level. Total zooplankton abundance reached its maximum in spring and summer. The δ13C values of copepods showed statistically significant differences both between stations and seasons. As a selective feeder, C. helgolandicus had the highest values in both δ13C and δ15N. Being a filter feeder, P. avirostris distinctly differed from C. helgolandicus and A. clausi. Enrichment was observed in δ15N values of copepods in winter, when the highest values of total suspended solids and chlorophyll-a were determined. The results showed that δ13C values of the copepods were under the influence of environmental and biological factors. Additionally, dietary differences between herbivorous groups and other groups were clearly demonstrated, as well as differences in the diets of filter-feeding and selectively-feeding zooplanktonic species. https://doi.org/10.2298/ABS181003059U Received: October 3, 2018; Revised: November 30, 2018; Accepted: December 18, 2018; Published online: December 27, 2018 How to cite this article: Uzundumlu S, Büyükateş Y. Stable isotope compositions of dominant zooplankton species in relation to environmental factors in the Dardanelles. Arch Biol Sci. 2019;71(1):177-85.